PENGARUH KOMPETENSI SERTA BUDAYA KERJA TERHADAP KINERJA PEGAWAI YANG DIMEDIASI OLEH MOTIVASI KERJA DI DINAS PERKEBUNAN PROVINSI SUMATERA SELATAN - Abelia, Shinta Elpatrika; Hakimah, Yusro; Veybitha, Yolanda (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2025)
This study aims to examine the influence of Competence and Work Culture on Employee Performance at the Plantation Office of South Sumatra Province, both directly and indirectly through Work Motivation as a mediating variable. The population in this study consisted of all 82 employees at the office, and the census method was applied, meaning the entire population was used as the sample. Data analysis was conducted using the Structural Equation Modeling (SEM) approach with Partial Least Squares (PLS) software. The results show that Competence significantly influences Work Motivation, as does Work Culture. Both Competence and Work Culture also have a significant effect on Employee Performance. Moreover, Work Motivation was found to significantly influence Employee Performance. The study further identified indirect effects, where Work Motivation partially mediates the relationship between Competence and Employee Performance, and fully mediates the relationship between Work Culture and Employee Performance.The R² value for the latent variable Work Motivation is 0.787, indicating that approximately 78.7% of the variation in Work Motivation can be explained by Competence and Work Culture, while the remaining 21.3% is influenced by other factors not included in this study. Meanwhile, the R² value for Employee Performance is 0.898, suggesting that around 89.8% of the variation in Employee Performance can be explained by a combination of Competence, Work Culture, and Work Motivation, with the remaining 10.2% influenced by external factors outside the model. This study recommends that the Plantation Office of South Sumatra Province continue to enhance employee competence through relevant training programs, foster a disciplined and innovative work culture, and strengthen work motivation through fair reward systems, clear career development opportunities, and transparent workload distribution. These efforts are essential to improving employee performance in a sustainable and optimal manner.